'Doing Evil' as Maiestas in John 18.301. (March 2020) - Wassell, Blake
The argument of this article is that in Jn 18.30 Jesus is accused of 'doing evil' to Caesar – or maiestas. Johannine critics sometimes mention maiestas, but they have neither introduced the ancient and modern literature on the topic nor applied it to the interpretation of the accusation against Jesus in John's gospel. Horace, Velleius Paterculus, the senatus consultum de Cn. Pisone patre and Suetonius, as well as various treaties and edicts, demonstrate the transference of maiestas from Rome to Caesar. So instead of slandering the people, the crime of maiestas became slandering the emperor. If an author such as Josephus seems, in his own way, to intimate the crime, then so also may John. And if 'doing evil' means maiestas, then Jn 18.30 ﬁts more comfortably not only with the wider ﬁrst century, but also the wider Johannine narrative.